2016
DOI: 10.1186/s13638-016-0705-2
|View full text |Cite
|
Sign up to set email alerts
|

An efficient traceable access control scheme with reliable key delegation in mobile cloud computing

Abstract: With the increasing number of mobile applications and the popularity of cloud computing, the combination of these two techniques that named mobile cloud computing (MCC) attracts great attention in recent years. However, due to the risks associated with security and privacy, mobility security protection in MCC has become an important issue. In this paper, we propose an efficient traceable access control scheme with reliable key delegation named KD-TABE in MCC. Firstly, we present a traceable CP-ABE system and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Other schemes in Table 2 are small universe schemes, where the public parameter size in our scheme is around 2l shorter than that in [18] and is second only to that in [10]. It is observed that the ciphertext size in [10] and [20] grows linearly with 2 , that the ciphertext size in our scheme and [14] grows linearly with 3 , and that the ciphertext size in [17] grows linearly with 6 . Thus, the ciphertext size in our scheme is the same as that in [14], and is slightly larger than that in [10] and [20], and is much smaller than that in [17] and [18].…”
Section: Scheme Analysis a Performance Analysismentioning
confidence: 65%
See 2 more Smart Citations
“…Other schemes in Table 2 are small universe schemes, where the public parameter size in our scheme is around 2l shorter than that in [18] and is second only to that in [10]. It is observed that the ciphertext size in [10] and [20] grows linearly with 2 , that the ciphertext size in our scheme and [14] grows linearly with 3 , and that the ciphertext size in [17] grows linearly with 6 . Thus, the ciphertext size in our scheme is the same as that in [14], and is slightly larger than that in [10] and [20], and is much smaller than that in [17] and [18].…”
Section: Scheme Analysis a Performance Analysismentioning
confidence: 65%
“…However, their scheme only supports an AND gate access structure, and the size of ciphertext and user private key grows linearly with the size of the entire attribute universe, which makes the scheme inefficient. In addition, Ning et al proposed a traceable CP-ABE scheme realizing the public auditing [19], Guan et al's CP-ABE scheme achieved both traceability and reliable key delegation [20], and Li et al established a traceable CP-ABE scheme with the verifiable outsourced decryption [21].…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Ning et al [22] offered a CP-ABE scheme and achieved both public auditing and traceability. The scheme of Guan et al [23] realized traceability and brought about reliable key delegation. Li et al [24] provided a CP-ABE scheme with traceable and the outsourced decryption with verifiable was realized at the same time.…”
Section: A Related Workmentioning
confidence: 99%
“…In order to provide an efficient traceable access control in a mobile cloud computing environment, Guan et al, in "An efficient traceable access control scheme with reliable key delegation in mobile cloud computing" [9], construct a traceable CP-ABE system with the access tree and realize the key delegation at servers without loss of traceability and then propose a new type of reencryption method, which is based on an intuitive method that supports any monotonic access tree.…”
Section: Mobility Security and Privacy Protectionmentioning
confidence: 99%